Penerapan Strategi Pengembangan Bisnis Usaha Ternak Ayam Dalam Perspektif Teoritis - Siti Muntamah; Dety Mulyanti (Jurnal Publikasi Ilmu Manajemen, 2023)
A business development strategy is a priority plan to achieve these goals or a business venture. One of the businesses in the livestock sector that has the potential to generate large profits is the chicken farming business. The purpose of this theoretical review is to find out how the chicken farming business development strategy is. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are that in implementing a business business development strategy, product development, market development, concentrated development and innovation development are needed. It can be concluded that the livestock business development strategy is a group of policies, plans, objectives and business activities or companies that aim to identify business opportunities and maintain business continuity so as to achieve the targets desired by business actors. Business development in the livestock sector is also one of the efforts made by business owners to increase their business profitability or business ability to generate more profits. For business actors in the livestock sector, they must always develop a business that covers the scope of the entire business in order to be able to create business synergies in order to realize successful long-term business development.